Commencement, Northeast Missouri State University, Kirksville, Mo., December 18, 1993 - Northeast Missouri State University (Kirksville, Mo.) (1993)
This commencement program shows the honor and senior class on December 18, 1993 at the Northeast Missouri State University in Kirksville, MO